PENGARUH MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL WIJEN HITAM DAN WIJEN PUTIH (Sesamum indicum L.) - , NURMASARI FITRISIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One marginal land that shows high potential for agriculture is a sandy soil. Many problems are found in sandy soil, both in physical, chemical and biological characteristics. Farm yard manures are believed to be able to improve soil biological, chemical and physical characteristics, therefore research is carried out to determine the effect of cow, chickens, and goat manure fertilizers on growth, quantity and quality yield of white and black sesame. This research was conducted at Tridarma Farm Station, Agriculture Faculty, Gadjah Mada University, located in Banguntapan, Bantul, Yogyakarta from March until July 2012. The design of experiments was factorial Completely Randomized Design. The first factor was 5 kinds of fertilizers consisted of without fertilizer, cow manure, chicken manure, goat manure and inorganic fertilizer. The second factor was two kinds of sesame cultivars consisted of white sesame and black sesame. Data were analyzed with analysis of variance Î± = 5%. If there was significantly difference, interaction and mean effects were compared with Duncan Newâs Multiple Range Test and planned test at Î± = 5 %. The results showed that the application of manure fertilizer can increase the plant height of black sesame, number of branches, number of pods, dry weight at 4 and 14 weeks after planting, root volume, oil content and harvest index compared to the application of inorganic fertilizer. Seed weight per plant of white sesame on chicken manure treatment is 41.37 % higher than goat manure treatment but it is not significantly different with cow manure. White sesame seed oil content with the application of goat manure is higher 2.7% than control.